2014
DOI: 10.1103/physrevb.90.125134
|View full text |Cite
|
Sign up to set email alerts
|

Electrical resistivity of single crystals of LaFeAsO under applied pressure

Abstract: Measurements of electrical resistivity under applied pressure were performed on single crystalline samples of LaFeAsO grown in a molten NaAs flux. We observe a smooth suppression of spin-density wave order under nearly hydrostatic applied pressures up to 2.6 GPa and in quasi-hydrostatic pressures up to 14.7 GPa. Similar to some of the other reports on single and polycrystalline samples of LaFeAsO, these crystals exhibit a resistivity that increases as temperature is lowered. By fitting an Arrhenius law to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…We found that among different samples the magnetic phase transition temperature as well as the low-temperature magnetic hyperfine field decrease with increasing unit cell volume which might explain the difference in the observed quantities. Interestingly the behavior of both LaFeAsO single crystals 10,30,31,41,42 and polycrystalline samples 8,9,16,33 are consistent within each other.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…We found that among different samples the magnetic phase transition temperature as well as the low-temperature magnetic hyperfine field decrease with increasing unit cell volume which might explain the difference in the observed quantities. Interestingly the behavior of both LaFeAsO single crystals 10,30,31,41,42 and polycrystalline samples 8,9,16,33 are consistent within each other.…”
Section: Discussionsupporting
confidence: 67%
“…It was pointed out by McElroy et al that in polycrystalline samples the reduction in the resistivity at lower temperatures is very broad and it goes to zero only at 12 GPa which is maybe caused by tiny amounts of O-deficient sample volumes. 10,33 Mössbauer measurements by Nowik et al on O-deficient LaFeAsO have shown that Fe in the vicinity of an O vacancy has a small magnetic hyperfine field of ∼ 0.8 T but a huge quadrupole splitting of ∼ −0.86 mm/s at low temperatures. 39 In the Mössbauer experiments under pressure of the polycrystalline samples no O-deficiency was detected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More reliable results can be obtained in 1111 single crystals. A recent high-pressure experiment on single-crystal LaFeAsO grown using a NaAs flux shows no bulk superconductivity up to 37 GPa [15,16], which strongly contradicts polycrystalline sample measurements, which show SC under pressure in a wide dome with a maximum T c of ∼22 K under 12 GPa [12]. This discrepancy may be induced by the difference in the samples grown in their respective synthesis conditions.…”
Section: Introductionmentioning
confidence: 86%
“…Indeed, in the T −P phase diagram of FeSe, superconducting phase coexists with nematic phase for 0≤P ≤1.5 GPa and with dome-shaped AFM phase for 1.5≤P ≤6 GPa but highly enhanced above 6 GPa [2,3]. In RFeAsO 1−x F x (R=lanthanide), the T -P phase diagram however remains solved, although several studies have been conducted for R=La [4,5,6], Ce [7,8]. To study the relationship between the superconducting and other two phases in the phase diagram of RFeAsO 1−x F x , we need to prepare lightly doped specimens so that the superconductivity is induced only above a critical pressure P c , since the SDW and nematic phases do not appear in optimally doped superconducting specimens.…”
Section: Introductionmentioning
confidence: 99%